ILMU KALIGRAFI DAN PERANANNYA - Dwi Lestari; Rani Nura'ini; Nabil Mahmudi Siregar; Lailatul Husna Efendi (Jurnal Ekshis, 2024)
Calligraphy is considered an ancient discussion today, but it is an art that purely emerged from Islam itself. The development of calligraphy in Islam is largely due to the emergence of the Qur'an. The writing of the Qur'an in Arabic made calligraphy a distinctly Islamic art. So Muslims are required to learn Arabic, but learning Arabic requires four language skills, namely listening skills, speaking skills, reading skills, and writing skills. Writing skills are the basis of the development of calligraphy in Islam. Calligraphy is the art of writing beautifully, therefore, researchers wrote in this journal about the effect of calligraphy on writing proficiency in Arabic. The method used in writing is the literature review method by analyzing various references. Based on the results of the analysis, the effect of calligraphy on Arabic language skills can train the spontaneity and quality of writing of students.